2018
DOI: 10.1038/s41416-018-0249-9
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically regulated miR-1247 functions as a novel tumour suppressor via MYCBP2 in methylator colon cancers

Abstract: Background Colorectal cancer (CRC) is a heterogeneous disease with distinct clinical subsets based on underlying genetic and epigenetic changes. DNA hypermethylation yields a unique CRC subset with a distinct phenotype and clinical behaviour, but this oncogenic pathway is not fully characterised. This study identifies and characterises miR-1247 as a novel tumour suppressor microRNA in methylated human colon cancers. Method Tumour samples from patients with hypermethylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…When overlapping the data from NwCRC, Ob, and ObCRC individuals, the down-regulation of miRNAs, such as miR-193b-3p, miR-125a-5p, and miR-1247-5p, was found to be shared between cancer and obese conditions. Interestingly, both miR-193b-3p, and miR-1247-5p act as tumor suppressors in CRC or other types of cancer ( 71 , 72 ), suggesting that their repression in AT from Ob and CRC individuals could have a potential pro-tumorigenic role. Beside common features, some ncRNAs are unique of tumor conditions.…”
Section: Discussionmentioning
confidence: 99%
“…When overlapping the data from NwCRC, Ob, and ObCRC individuals, the down-regulation of miRNAs, such as miR-193b-3p, miR-125a-5p, and miR-1247-5p, was found to be shared between cancer and obese conditions. Interestingly, both miR-193b-3p, and miR-1247-5p act as tumor suppressors in CRC or other types of cancer ( 71 , 72 ), suggesting that their repression in AT from Ob and CRC individuals could have a potential pro-tumorigenic role. Beside common features, some ncRNAs are unique of tumor conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As to the down-regulation of miR-1247 in 11/35 of our CRC patients, it is similarly consistent with a predominant tumor suppressor function that is well established in a variety of tumors, including CRC [ 52 , 53 , 54 , 55 , 56 , 57 ]. The MYCBP2/c-myc axis may underlie the anti-tumor activities of miR-1247 [ 58 ]. However, we also observed up-regulation in seven cases, a finding that deserves further functional studies.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that msi-h could be a potential prognostic and therapeutic factor for COAD [ 47 ], which suggested that msi-h could play important roles for the patients in subtype c3 with msi-h. OBSCN , RYR2 and TTN mutations which have been reported as drivers [ 48 ] could be biomarkers for subtype c3. And more, MYCBP2 was reported as a potential therapeutic target for CRC [ 49 ], which could offer treatment suggestions for subtype c3. Therefore, for patients in subtype c3, spliceosome, antigen processing and presentation, estrogen signaling pathway, NMD, msi-h, OBSCN , MYCBP2 , RYR2 , and TTN could be the potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%